Pendampingan Literasi Finansial Rumah Tangga Masyarakat Dusun Kawan Kabupaten Bengkayang - William Wendy Ary; Helena Anggraeni Tjondro Sugianto; Aloysius Hari Kristianto (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Indonesia is a country that has been categorized as one of G-20 countries and also indeed has a high level of economy globally. Financial Industry is one of the sectors that contributes Indonesian economy. However, even though the financial sector is one of the biggest contributors, there are still many Indonesia’s citizens who are not with financially iterated, especially in Bengkayang Regency and this problem has motivated the community service team of the Shanti Bhuana Institute to carry out community service activities in Kawan Hamlet in Bengkayang Regency. This activity uses three methods, namely lectures, tutorials and practices. This service activity received both satisfying results where 54.5% of the participants felt quite satisfied with the service activities that had been carried out and the remaining 45.5% were very satisfied with the implementation of community service activities. A total of 33 participants said they understood the whole material in the range of 76-100%, 8 participants said they understood the whole material in the range of 50-75%, and only 2 participants said they understood the whole material in the range below 50%